PENETAPAN UANG PANAI BERDASARKAN MUSYAWARAH PADA MASYARAKAT BUGIS DI KELURAHAN SAIGON, KOTA PONTIANAK - Putri Irda Ardha; Muhammad Hasan; Dwita Wahyuni (Al-Usroh, 2025)
This research aims to: 1) investigate the determination of uang panai among the Bugis nobility in Saigon Sub-District, East Pontianak; 2) analyze the determination of uang panai among the non-noble class in the same location; and 3) explore the application of the deliberation principle in the determination process.The study employs a qualitative approach with a descriptive-analytical field research design.Primary data were collected through in-depth interviews and documentation with customary leaders, religious figures, and members of the Bugis community from both social strata.Secondary data were sourced from relevant academic literature.Data were analyzed thematically to identify patterns and meanings behind the existing practices.The results indicate that among 1).the nobility, uang panai is determined based on lineage, noble titles, and educational level, with values that can reach hundreds of millions of rupiah as a symbol of honor and social responsibility.2).among the non-noble class, the determination of uang panai is more flexible, adapting to economic conditions and emphasizing the appreciation of the groom's education and seriousness.3).The principle of deliberation is found to play a crucial role in both strata as a mechanism for reaching a mutual agreement without coercion, albeit influenced differently by social status factors.These findings contribute to the discourse on harmonizing customary law, Islamic values, and social reality within a pluralistic society.